A Comparative Analysis of Family Quality of Life Between Heterosexual and Sexual Minority Caregivers of People with Dementia. (June 2022) - Anderson, Joel G.; Jabson Tree, Jennifer M.; Flatt, Jason D.; Gross, Alden L.; Williams, Ishan C.; Rose, Karen M.
Providing care for someone with Alzheimer's disease or related dementias (ADRD) is associated with significant physical and mental strain affecting quality of life among caregivers. However, little attention has been given to sexual minority (SM; lesbian, gay, bisexual, queer) people caring for those with ADRD. In this cross-sectional study, we used psychosocial measures to describe the characteristics and family quality of life of SM and heterosexual caregivers for people with ADRD. SM caregivers were significantly younger and more frequently reported full or part-time employment compared with their heterosexual counterparts. Lesbian and bisexual caregivers reported more difficulty in paying for everyday basics. After controlling for demographic covariates, SM caregivers had significantly higher family quality of life scores compared with heterosexual caregivers. This study is among the first to compare family quality of life between SM and heterosexual caregivers. Findings can guide development of targeted interventions for SM caregivers.